2017
DOI: 10.1111/ibi.12500
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and diversification of an Amazonian understorey hummingbird: paraphyly and evidence for widespread cryptic speciation in the Plio‐Pleistocene

Abstract: Straight-billed Hermit Phaethornis bourcieri inhabits the understorey of upland terra firme forest throughout most of the Amazon basin. Currently, two allopatric taxa regarded as subspecies are recognized: P. b. bourcieri and P. b. major. However, the validity, interspecific limits and evolutionary history of these taxa are not yet fully elucidated. We use molecular characters to propose a phylogenetic hypothesis for populations and taxa grouped under Phaethornis bourcieri. Our results showed that P. bourcieri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
2
4
1
Order By: Relevance
“…The distribution of these clades corresponds to the southern and northern margins of the Solimões-Amazon River, respectively. The variation in this estimate (0.5-1.3 mya) is consistent with those of other groups of Amazonian birds (Araújo- Silva, Miranda, Carneiro, & Aleixo, 2017;Fernandes, Wink, & Aleixo, 2012;Ribas et al, 2012;Thom &Aleixo, 2015) and the formation of the upper Amazon River, between the upper Pliocene and lower Pleistocene (Campbell, Frailey, & Romero-Pittman, 2006;Hoorn et al, 2010;Latrubesse et al, 2010).…”
Section: Biogeographic Events and The Diversification Of The Lepidosupporting
confidence: 88%
“…The distribution of these clades corresponds to the southern and northern margins of the Solimões-Amazon River, respectively. The variation in this estimate (0.5-1.3 mya) is consistent with those of other groups of Amazonian birds (Araújo- Silva, Miranda, Carneiro, & Aleixo, 2017;Fernandes, Wink, & Aleixo, 2012;Ribas et al, 2012;Thom &Aleixo, 2015) and the formation of the upper Amazon River, between the upper Pliocene and lower Pleistocene (Campbell, Frailey, & Romero-Pittman, 2006;Hoorn et al, 2010;Latrubesse et al, 2010).…”
Section: Biogeographic Events and The Diversification Of The Lepidosupporting
confidence: 88%
“…Interestingly, despite the existence of a phylogeographical structure, most geographical lineages were not reciprocally monophyletic, indicating a lack of complete lineage sorting probably due to recent differentiation. This phylogeographical pattern is intermediate between that detected for typical understorey upland terra firma species, which almost invariably show high degrees of phylogeographical structure (Capurucho et al , Thom & Aleixo , Araújo‐Silva et al ), and that uncovered for seasonally flooded forest taxa, which exhibit little or no phylogeographical structure across large areas (Aleixo , Cadena et al ).…”
Section: Discussioncontrasting
confidence: 55%
“…The six major geographical lineages identified in the estimated phylogenies and the parsimony network for A. taciturnus provide evidence for significant genetic structure across major morphoclimatic domains and interfluves in northern South America. The species tree topology for A. taciturnus comprises analogous area relationships to other phylogenetic studies (Aleixo & Rossetti , Martins et al , Milá et al , Harvey & Brumfield , Rocha et al , Araújo‐Silva et al ). The incomplete sorting of alleles observed in the dataset is associated with a possible secondary contact between lineages of the Atlantic Forest, Caatinga and the central Tapajós–Xingu Interfluve (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Phylogeographic studies have helped define interspecific boundaries and shed light on the spatio-temporal patterns of diversification of several Amazonian taxa (Aleixo, 2002(Aleixo, , 2004Marks et al, 2002;Ribas et al, 2006Ribas et al, , 2012Lavergne et al, 2010;Avila-Pires et al, 2012;Carneiro et al, 2012;Batista et al, 2013;Fouquet et al, 2015;Mercês et al, 2015;Thom and Aleixo, 2015;Araújo-Silva et al, 2017;Sampaio et al, 2018;Capurucho et al, 2020;Dantas et al, 2021). These phylogeographic studies confirmed the effect imposed by major Amazonian rivers, inhibiting gene flow between allopatric populations and closely related species, and hence, delimiting interfluves as areas of endemism or endemism center (Silva et al, 2005;Ribas et al, 2012;Batista et al, 2013;Maldonado-Coelho et al, 2013;Thom and Aleixo, 2015).…”
Section: Introductionmentioning
confidence: 94%